Hepatitis E Virus infection among Asymptomatic pregnant women at the University College Hospital, Ibadan (2020)
Introduction: The high mortality associated with fulminant Hepatitis E infection in pregnancy justifies the need to assess the epidemiologic proportion of this underestimated virus. Objectives: This study aimed to determine the burden of HEV infection among pregnant women attending antenatal Clinic in Ibadan. Methodology: HEV IgG and IgM serological surveys were carried out among 230 pregnant women attending antenatal clinic in Ibadan, Nigeria. Serum and stool samples from HEV IgM positive women were further analysed using two independent reverse transcriptase polymerase chain reactions (RT‑PCR) assays, targeting ORF1 region of HEV genome. Socio‑demographic variables associated with HEV in these women, were analyzed to estimate statistical significance (p < 0.05). Results: Eleven (4.8%) women had HEV IgM, while 39 (17.0%) women had HEV IgG. Three (27.3%) of the 11 anti‑HEV IgM positive samples were positive for HEV RNA while all stool samples tested negative for HEV RNA. HEV infection among pregnant women was statistically associated with age (p = 0.044), and educational status (p = 0.005). Conclusion: Recent HEV infection among this pregnant population is on the lower part of the scale, compared with other Sub‑Saharan African countries. However, the HEV IgG seroprevalence rate suggests indirect evidence of past contact with HEV.